Archiving Application High Military Court Case I Medan Mobile Based - Andi Juandi Saputra; R. I. E. Saragih; Gortap Lumbantoruan (Geviva Publisher, 2022)
Application is an indispensable necessity at this time. A company or agency requires the role of information technology in terms of data management, one of which is the management of records. Archive is a recording of activities or events in various forms and media in accordance with the development of information and communication technology created and received by state institutions, regional governments, educational institutions, companies, political organizations and others that support the smooth operation of a company or agency. Information technology systems are needed to speed up the work process, reduce material waste, facilitate management so that archived data is well and regularly maintained in a system, and when data is needed can be found easily and quickly. With the development of increasingly sophisticated technology in the current era of globalization, we need a system that can facilitate all problems. The archiving problem can be overcome by having an application that can be used by the case administrator. Application for archiving that can be reached anywhere while being needed by the case administrator. The application can also make it easier to find data that is needed. At this writing will also explain the stages of research, starting from the analysis process, planning and implementing.